Characterization of the Molecular Mechanisms of Resistance against DMI Fungicides in Cercospora beticola Populations from the Czech Republic - Kumar, Ram; Mazakova, Jana; Ali, Asad; Sur, Vishma Pratap; Sen, Madhab Kumar; Bolton, Melvin D; Manasova, Marie; Rysanek, Pavel; Zouhar, Miloslav (Journal of fungi (Basel, Switzerland), 2021)
Cercospora leaf spot (CLS), caused by the fungal pathogen Cercospora beticola, is the most important foliar pathogen of sugar beet worldwide. Extensive reliance on fungicides to manage CLS has resulted in the evolution of fungicide resistance in C. beticola worldwide, including populations in the Czech Republic. One important class of fungicides used to manage CLS is the sterol demethylation inhibitors (DMI). The aim of our study was to assess DMI resistance in C. beticola from the Czech Republic and elucidate the molecular basis of DMI resistance in this population. A total of 50 isolates were collected in 2018 and 2019 from the major sugar beet growing regions of the Czech Republic and assessed for in vitro sensitivity to the DMI fungicides propiconazole, prochloraz, and epoxiconazole. These analyses identified three strains that exhibited 50% effective concentration (EC50) values > 1.0 μg mL-1 against respective fungicides, which were therefore considered resistant. In contrast, strains that exhibited lowest EC50 values were considered sensitive. To explore the molecular basis of resistance in these three strains, the cytochrome P450-dependent sterol 14α-demethylase (Cyp51) gene was sequenced. Sequence analysis identified a Y464S mutation in all three resistant strains. To assess whether Cyp51 gene expression may play a role in DMI resistance, selected strains were grown in vitro with and without fungicide treatment. These analyses indicated that Cyp51 gene expression was significantly induced after fungicide treatment. Thus, we conclude that Y464S point mutation along with induced Cyp51 gene overexpression is likely responsible for resistance against DMI fungicides in C. beticola from the Czech Republic.
Keywords: Cercospora beticola; Cyp51; DMI fungicide resistance; molecular dynamics simulations; real-time PCR